Water in Kentucky - Krieger, Robert A. (Robert Albert), 1918-2006 (Book collections on Project MUSE., 1969)
Lakes, rivers, and springs have shaped and nourished life in Kentucky for centuries, and water has played a pivotal role in determining Kentucky's physical, cultural, and economic landscapes. In this generously illustrated work, experts from a variety of fields explain how water has defined regions across the state.